21st-century digital skills instrument aimed at working professionals: Conceptual development and empirical validation - van Laar, Ester; van Deursen, Alexander J.A.M.; van Dijk, Jan A.G.M.; de Haan, Jos (Telematics and informatics, 2018)
•We set out to develop measures for assessing 21st-century digital skills.•We took a three-fold approach: cognitive interviews, a survey pilot and a full survey.•The final sample included 907 professionals working within the creative industries.•The result is a validated instrument for measuring six types of 21st-century digital skills. Employees with high levels of 21st-century digital skills are beneficial for organizations characterized by rapid technological changes and complex knowledge bases. Although a number of instruments have been used to measure digital skills, they do not consider the broad range of 21st-century skills. Additionally, available measures are limited by their use of agreement scales and by their primary focus on students or citizens. This study aims to overcome these limitations by developing a set of reliable measures that focuses on the frequency of activities performed by working professionals to assess each core 21st-century digital skill. To this end, we conducted cognitive interviews, a survey pilot, and a full survey among a large sample of professionals working within the creative industries. The result is a theoretical, empirically validated instrument that measures six types of 21st-century digital skills: information, communication, collaboration, critical-thinking, creativity, and problem-solving skills.